2017
DOI: 10.1148/rg.2017170035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical PET Imaging in Prostate Cancer

Abstract: Prostate cancer is the second most common cancer in men worldwide, with a wide spectrum of biologic behavior ranging from indolent low-risk disease to highly aggressive castration-resistant prostate cancer. Conventional imaging with computed tomography, magnetic resonance imaging, and bone scintigraphy is limited for the detection of nodal disease and distant bone metastases. In addition, advances in the available therapeutic options, both localized and systemic, drive the requirement for precise diagnostic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
75
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 109 publications
(207 reference statements)
0
75
0
5
Order By: Relevance
“…With respect to tumor imaging, most of the subjects exhibited an overall radiologic response of the stable disease. One of the reasons for this modest response could be the limitations associated with conventional imaging in staging, restaging after biochemical relapse, and response assessment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to tumor imaging, most of the subjects exhibited an overall radiologic response of the stable disease. One of the reasons for this modest response could be the limitations associated with conventional imaging in staging, restaging after biochemical relapse, and response assessment …”
Section: Discussionmentioning
confidence: 99%
“…for this modest response could be the limitations associated with conventional imaging in staging, restaging after biochemical relapse, and response assessment. 29 Shortly after the initiation of this study, the dose of PSMA ADC was reduced from 2.5 to 2.3 mg/kg due to dose-limiting toxicities (eg, neutropenia and sepsis), which were occurring during the first 3 weeks of treatment (cycle 1). These toxicities have also been reported with other ADCs utilizing MMAE, such as brentuximab vedotin and glembatumumab vedotin.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely utilized radiotracer in cancer imaging is F-18-labeled fluoro-2-deoxyglucose (F-18-FDG) in conjunction with PET/CT [12]. The typical appearance of a liposarcoma on F-18-FDG PET/CT varies based upon its internal components and degree of heterogeneity, however, a study by Rahkeja et al demonstrated that a greater degree of radiotracer uptake (established by higher maximum standard uptake values [SUV max ]) correlated with mitotic count and tumor necrosis within a liposarcoma [13].…”
Section: Imaging Appearancementioning
confidence: 99%
“…An additional PET radiotracer typically utilized for biochemical prostate cancer recurrence is the amino acid analogue F-18-fluciclovine, whose mechanism capitalizes on the increased transport and metabolism of amino acids within cancer cells [12]. The uptake of the radiotracer F-18-fluciclovine, however, is nonspecific for prostate cancer and can be seen in benign entities like prostatic hyperplasia though is thought to be advantageous for local prostate cancer recurrence following prostatectomy given its low accumulation of radiotracer within the bladder [12,14]. Additional cases of F-18-fluciclovine's nonspecific uptake have been described in several other entities such as pituitary adenomas, meningiomas, and malignancies such as breast cancer [12,14].…”
Section: Imaging Appearancementioning
confidence: 99%
“…Reviews detailing the importance and discovery of new molecular biomarkers 8 for prognosis and the currently used diagnostics and therapeutics 9,10 for PCa have been published. In 2018, refined advances in prostate-specific membrane antigen (PSMA)targeted PET/CT imaging techniques [11][12][13][14][15] using various positron emission radioisotopes for early detection of PCa, management of metastatic castration-resistant prostate cancer (mCRPC), and their applications in detection of recurrent disease by guided biopsy and surgery 16 were published. There are also recent reports that exclusively cover clinical translation of PSMA-targeted 68 Ga and 177 Lu radioisotopes for detection and therapy of PCa in humans.…”
mentioning
confidence: 99%